Role of amniotic fluid index on maternal and neonatal outcomes among obstetric women with preterm premature rupture of membranes - Britto J., Jennifer; R., Sailatha; Nalini, Amrita Priscilla (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Preterm Premature rupture of Membrane (PPROM) is one of the major complications of a pregnant women with risk factors like low socioeconomic class, infections, STDs etc. Maternal complications such as Chorioamnionitis, Abruptio placenta, sepsis and neonatal complications like neonatal sepsis, RDS, intraventricular hemorrhage are common with those with PPROM. The objectives of the present study were to find the association between AFI values and maternal and fetal outcomes in patients with preterm premature rupture of membranes Methods: A cross sectional study was conducted in a Multispecialty Teaching Hospital, North Chennai, Tamil Nadu with the sample size of 100. The study participants included pregnant women with gestational age of 28 to 34 weeks presenting with PPROM. Maternal outcomes included clinical diagnosis of chorioamnionitis, placental abruption, meconium in liquor, fetal distress, prolapsed cord and mode of delivery. Neonatal outcomes include neonatal hospitalization in NICU, APGAR score at 1st minute and 5 minutes, early neonatal sepsis neonatal death. Significance of difference in means was calculated using independent t test. Results: Total study participants were divided into 2 groups with Amniotic Fluid Index (AFI) of >5 and <5. Latency period, Chorioamnionitis, placental abruption and mode of delivery were compared between the groups. Chorioamnionitis was present in 8% and 12% in group 1 and group 2 respectively. Neonatal outcomes like NICU admission, RDS and neonatal sepsis were also compared between the groups. NICU admission was required for 18% and 48% in group 1 and 2 respectively. APGAR scores at 1 and 5 minutes were found to be lower among those with Group 2. (p =0.000). Conclusions: PROM is associated with increased maternal and neonatal complications. AFI has been proven a role in predicting maternal and neonatal outcomes in PROM. Identifying the risk factor and its treatment remains the main mode of prevention for PROM.